2022
DOI: 10.1111/1556-4029.15117
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of paranasal sinus measurements on multislice computed tomography for sex estimation: A systematic review, meta‐analysis, and meta‐regression

Abstract: This systematic review aimed to answer the question, "Are paranasal measurements obtained with multislice computed tomography able to accurately estimate sex?" This PROSPERO-registered systematic review included six databases and gray literature.Meta-analysis of linear and volumetric data was performed using a random-effects model, mean differences (MDs), and inverse variance. The QUADAS-2 tool-related risk of bias (RoB) and certainty evidence (GRADE approach) were assessed. A total of 1651 articles were initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 103 publications
(217 reference statements)
0
0
0
Order By: Relevance
“…Because of the unique structures of the paranasal sinuses, forensic identification has demonstrated its effectiveness, particularly in determining sex. 2 Paranasal sinuses are complex anatomical structures that exhibit a highly variable shape, morphology, and size. 1 It has been stated that comprehending the structural variations of the paranasal sinuses and the potential implications of their varying sizes are crucial for surgeons and radiologists to understand sinus pathology and devise the most effective treatment.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Because of the unique structures of the paranasal sinuses, forensic identification has demonstrated its effectiveness, particularly in determining sex. 2 Paranasal sinuses are complex anatomical structures that exhibit a highly variable shape, morphology, and size. 1 It has been stated that comprehending the structural variations of the paranasal sinuses and the potential implications of their varying sizes are crucial for surgeons and radiologists to understand sinus pathology and devise the most effective treatment.…”
mentioning
confidence: 99%
“…1 Moreover, linear and volumetric measurements of the frontal and maxillary sinuses, because of their unique structure, have the potential to be utilized in forensic identification, particularly in determining an individual's sex. 2 Comparing antemortem and postmortem paranasal sinus radiographs and computed tomography (CT) scans of potential matches and human remains can aid in identification when methods such as fingerprints and DNA analysis are not viable because of issues such as decomposition, deterioration, or burning 3 and when dental comparison is also not applicable because antemortem records are not available. 4 It has been reported that the anatomical features of the sinuses, particularly the frontal sinuses, which exhibit diverse morphological characteristics in each individual, can be used as a form of identification, similar to fingerprints.…”
mentioning
confidence: 99%
See 3 more Smart Citations